THE RELATIONSHIP BETWEEN DENTAL AND ORAL HEALTH MAINTENANCE BEHAVIOR AND ORAL HYGIENE OF FIFTH GRADE STUDENTS AT SDN ALUE ACEH BESAR DISTRICT - Mufizarni; Reca; Salfiyadi, Teuku (Journal Dental Health, 2023)
Oral hygiene is one of the actions needed to keep the mouth from infection, clean and freshen the mouth. Awareness of maintaining dental and oral hygiene is very necessary as an effort to prevent dental and oral health problems. The purpose of this study was to determine the relationship between behavior and oral hygiene in fifth grade students at SDN Alue, Aceh Besar District. The research used is an analytical method with a cross sectional study design approach. The population in this study were all fifth graders at SDN Alue, totaling 40 respondents. The analysis carried out is univariate and bivariate analysis using chi-square statistical test. The results showed that from 40 respondents, it was found that knowledge of dental and oral health maintenance in the poor category was 21 respondents (52.5%), attitudes in the poor category were 23 respondents (57.5%), actions in the poor category were 25 respondents (62.5%). Dental and oral health maintenance behavior as knowledge (P=0.001), attitude (P=0.001) and action (P=0.002). Based on the results of the study, it can be concluded that there is a relationship between dental and oral health maintenance behavior with oral hygiene in fifth grade students at SDN Alue, Aceh Besar District. It is recommended for students to improve their behavior in maintaining their own oral and dental health.